Pengembangan Sistem Informasi Pencatatan dan Pelaporan Akupunktur di Poliklinik Akupunktur Rumah Sakit PKU Delanggu - Isnaini, Anjar; , Sri Darnoto S.KM M.PH; , Arief Kurniawan NP, SKM, M.PH (2015)
The Policlinic Acupuncture PKU Muhammadiyah Delanggu Hospital needs the system of recording and reporting data properly and accurately. Up to how the recording and processing of data activities run less than optimal, because there are still done manually, where the other policlinic have done the system of information, so when the officer arrange reporting, theyhae difficulties because they must record and look for the data before that will be need. The purposing this research is to do the development of system, with a draft system for recording and reporting of data on the Policlinic Acupuncture PKU Muhammadiyah Delanggu Hospital. This type of research is developing and researching with qualitative approach and system development. The development system method which used prototypemethod. This research sample consists of 2 acupuncture terapist, 1 medical record officer of out patient, and 1 Kasubag Kepegawaian (receiver reports officer).Results of user identification, researchers designed the 5 data flow diagram (DFD) is a diagram cortex recording and reporting information system of acupuncture, processing DFD data base recording and reporting of acupuncture, DFD recording patient data, DFD therapy techniques, DFD summary report the number of patients, entity relationship diagram (ERD), 15 table data base and 17 input system interface design: 16 and outputs: 1 (Summary Report Number of Patients). The developing system use PHP and MySQL data base.